2005
DOI: 10.1002/ajmg.a.30716
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal mucolipidosis type II (I‐cell disease) can present as Pacman dysplasia

Abstract: Pacman dysplasia has been previously reported to be a lethal skeletal dysplasia with epiphyseal stippling and osteoclastic overactivity. We report on a sibling of a fetus previously reported as Pacman dysplasia. This infant has a clinical course consistent with mucolipidosis type II (I‐cell disease) along with confirmatory biochemical, cytologic, and radiographic evidence. This case expands the phenotypic spectrum of mucolipidosis type II. Having redefined the diagnosis in one of the original cases of Pacman d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Several reports have described cases of ML II that expressed skeletal dysplasia prenatally 28,29) . In Lachman's study 29) , the most common disorders associated with fetal skeletal dysplasia were osteogenesis imperfect (18%), thanatophoric dysplasia (14%), campomelic dysplasia Ile1154GlnfsX3) (B).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described cases of ML II that expressed skeletal dysplasia prenatally 28,29) . In Lachman's study 29) , the most common disorders associated with fetal skeletal dysplasia were osteogenesis imperfect (18%), thanatophoric dysplasia (14%), campomelic dysplasia Ile1154GlnfsX3) (B).…”
Section: Discussionmentioning
confidence: 99%
“…40 The main postnatal manifestations of ML II include gradual coarsening of neonatally evident craniofacial features, early cessation of statural growth and neuromotor development, dysostosis multiplex, and major morbidity by hardening of soft connective tissue about the joints and in the cardiac valves. Fatal outcome occurs often before or in early childhood.…”
Section: Phenotypeegenotype Correlationsmentioning
confidence: 99%
“…A review of the literature identified a subset of patients with I-cell disease who presented in the neonatal period with features of “metabolic bone disease” rather than with the common signs of dysostosis multiplex that usually develop later in life. This presentation was accompanied by increased serum parathyroid hormone and alkaline phosphatase activity but normal calcium concentrations 3642…”
Section: Frequent Clinical Manifestations In the Neonatal Periodmentioning
confidence: 99%